Kontribusi Kekuatan, Koordinasi Mata-Tangan-Kaki dan Kelentukan Togok Terhadap Hasil Smash Bola Voli - Gilang Nuari Panggraita; Idah Tresnowati; Mega Widya Putri; Andung Dwi Haryanto (Jendela Olahraga, 2022)
Volleyball is a team sport, but the physical condition of an athlete will also affect the performance of teamwork. The purpose of this study is to look for large contributions of leg muscle strength, eye-hand-foot coordination and togok flexibility to the smash results of Pekalongan Regency volleyball athletes. this study is a quantitative study with a survey approach, with data analysis techniques using product moment correlation techniques with significant rates of 5% or 0.05. study results, (1) the results of the r-count of leg muscle strength test against smash results volleyball athletes by 0.827, (2) the results of the r-count of eye-hand-foot coordination tests against the results of smash volleyball athletes by 0.831, (3) the results of the r-count test of togok flexibility against the results of smash volleyball athletes by 0.580, (4) the results of the r-count test of leg muscle strength, eye-hand-foot coordination, flexing to the results of smash smash Volleyball athletes amounted to 0.929. In conclusion, there is a significant contribution between leg muscle strength, eye-hand-foot coordination, and togok flexibility to the smashresults. Advice, leg muscle strength exercises, eye-hand-foot coordination, togok flexibility can be used to improve volleyball athletes' smash results